Membangun Komunikasi Positif: Studi Kasus di TK Sabilul Huda - Nugraha, Anggi Purwa; Azizah, Rifa Fauziyatul (Sekolah Tinggi Ilmu Agama Islam Putra Galuh Ciamis, 2025)
This study explore positive communication strategies between teachers and parents at Sabilul Huda Kindergarten, as well as analyze their impact on child development and parental involvement. Using a qualitative approach with a case study method, data was collected through interviews, observation and documentation. The results showed that there are communication strategies such as socializing the vision, mission, school program and school soup, making pomg, maximizing multi-channel communication, making joint planning in learning, regular parent meetings, providing opportunities for parents to manage programs, making parents as guest teachers at school, building partnerships based on mutual understanding between the school and parents, challenges in building positive communication and the impact of positive communication on child development. The findings confirm the importance of empathic and structured communication in supporting early childhood education. This study recommends strengthening communication training and utilizing technology to improve the effectiveness of school-family partnerships.